Survival and movement of rehabilitated white‐tailed deer fawns in Connecticut - Scott C. Williams; Michael A. Gregonis (Wildlife Society Bulletin)
ABSTRACT Connecticut (USA) has a volunteer‐based, white‐tailed deer (Odocoileus virginianus) fawn rehabilitation program. In 2010 and 2011, 29 apparently orphaned or injured fawns were raised and released at about 3 months of age by licensed rehabilitators at no cost to taxpayers. Our objectives were to compare survival and movements of fawns subjected to 2 different release techniques. Thirteen fawns were soft‐released with feed and water provided ad libitum, and the remaining 16 were hard‐released into a 2,250‐ha block of state forest. Fawns were monitored daily using expandable radiocollars for 30 days and tri‐ or bi‐weekly thereafter. When mortality sensors activated, signs of trauma, struggle, hair, caching behavior, and scats were inspected to determine cause of death, and necropsies were performed in a laboratory for fawns evidently succumbing to sickness or starvation. Hard‐release fawns experienced 100% mortality within 35 days. Sources of mortality included coyote (Canis latrans), bobcat (Lynx rufus), vehicles, and pneumonia. Soft‐release fawns experienced 69% mortality within 86 days from coyote, vehicles, illegal shooting, and legal archery harvest. The Kaplan–Meier 100‐day survival rate for all fawns was 0.138 (SE = 0.064) for both years combined; 86% of fawns were dead within 86 days of release. All fawns exhibited high fidelity to release sites. Some soft‐release fawns survived longer by staying proximate to the pen, but in addition to unacceptably high mortality rates, all fawns, regardless of release technique, lacked the behavioral attributes needed by truly wild white‐tailed deer to survive to adulthood. © 2015 The Wildlife Society.